Identification of Suitable Telemetry Point Coordinates in Drone Video using Centroid Method for Precise Georeferencing - Nagpal, Vishal; Devare, Manoj H. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Vehicle detection is the most important aspect of traffic monitoring. Unmanned aerial vehicles (UAV) are used to calculate various traffic metrics such as traffic volume and density as well as to handle situations like accidents and traffic congestion in addition to monitoring traffic. The primary objective of this study is to examine the difficulties in accurately georeferencing drone videos to determine the speed of moving vehicles. This study also determined the ideal and minimal number of known telemetry points and their ideal location on video frames (images) in order to ensure accurate telemetry data calculations for all coordinates of the video frame. Since the globe is not flat and because drone payload, camera height, and slant angle might vary, most existing algorithms that use four corner points for georeferencing can be inaccurate. In order to overcome this drawback, the study suggests locating a fifth point coordinate and using it to compute a correction coefficient that can facilitate more precise telemetry point calculations. In addition to experimental data proving the efficiency of the suggested strategy in improving georeferencing accuracy, the study offers a thorough analysis of it. This study found that the centroid method improved data by 1% compared to the four-point approach and the fifth telemetry point in a drone video.